If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8.7 + -4.7(x + 2.3) = 7 + -3(x + 4) Reorder the terms: 8.7 + -4.7(2.3 + x) = 7 + -3(x + 4) 8.7 + (2.3 * -4.7 + x * -4.7) = 7 + -3(x + 4) 8.7 + (-10.81 + -4.7x) = 7 + -3(x + 4) Combine like terms: 8.7 + -10.81 = -2.11 -2.11 + -4.7x = 7 + -3(x + 4) Reorder the terms: -2.11 + -4.7x = 7 + -3(4 + x) -2.11 + -4.7x = 7 + (4 * -3 + x * -3) -2.11 + -4.7x = 7 + (-12 + -3x) Combine like terms: 7 + -12 = -5 -2.11 + -4.7x = -5 + -3x Solving -2.11 + -4.7x = -5 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -2.11 + -4.7x + 3x = -5 + -3x + 3x Combine like terms: -4.7x + 3x = -1.7x -2.11 + -1.7x = -5 + -3x + 3x Combine like terms: -3x + 3x = 0 -2.11 + -1.7x = -5 + 0 -2.11 + -1.7x = -5 Add '2.11' to each side of the equation. -2.11 + 2.11 + -1.7x = -5 + 2.11 Combine like terms: -2.11 + 2.11 = 0.00 0.00 + -1.7x = -5 + 2.11 -1.7x = -5 + 2.11 Combine like terms: -5 + 2.11 = -2.89 -1.7x = -2.89 Divide each side by '-1.7'. x = 1.7 Simplifying x = 1.7
| 5(2x-6)=30 | | 4ab-2b-2a= | | (132x)7-14x=0 | | 7x-2(x-5)=5(x+1)+8 | | 5x-9=5x+30-39 | | x-7=11/2 | | 7x-7x=25 | | x=20xy | | (x+7)*(x+3)= | | y=31292e(-0.2x) | | y=31292e-(9) | | (x+7)-(x+3)= | | 180=(180-(2x+60))+(3x+10)+x | | y=31292e-(0.2x) | | 180=(-180+(2x+60))+(3x+10)+x | | (x+7)+(x+3)= | | 180=(-180+2x+60)+(3x+10)+x | | 180=2x+3x+-180+60+10 | | 5(x-2)+4(x+2)=14-4x | | 4+-9x=9x+-2 | | 6=3sqrt | | 8x=-4x+-3x | | -16(t^2+4t+5)=0 | | d=1/16*8^2 | | d=1/16*7^2 | | d=1/16*9^2 | | d=1/16*60^2 | | d=1/16*20^2 | | 180=78+y+1.5y | | -1(4+x)=14 | | 7(x-2)+2(x+1)=1-3x | | 11x-2y=18 |